Post-fire response variability in Mediterranean Basin tree species in Portugal - Catry, Filipe X.; Pausas, Juli G.; Moreira, Francisco; Fernandes, Paulo M.; Rego, Francisco (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2013)
Fire is the most important natural disturbance driving vegetation dynamics in the Mediterranean Basin. However, studies relating fire-induced tree responses to both fire severity and plant traits are still scarce in this region. We aimed to investigate such relationships further and to develop simple models that could help improve forest management in these fire-prone ecosystems. We compiled data from 16 fire sites in different regions and used models to relate post-fire responses of 4155 trees from 14 species with fire severity indicators and tree characteristics. The influence of several spatiotemporal factors at the site level was also considered. Results showed that pine mortality was usually high and mainly determined by fire severity, whereas plant traits played a minor role. In contrast, mortality of broadleaved trees was usually low, even for high-severity fire, but most trees were top-killed. Stem mortality increased with fire severity and decreased with bark thickness and tree size. The models for predicting individual mortality of pines and stem mortality of broadleaves showed very good performance, including when validated against independent datasets. Our results suggest that it is possible to accurately predict the most common post-fire responses of Mediterranean species based on simple fire and tree characteristics.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: CSIRO PUBLISHING
Keywords: broadleaves; experimental fire; Modelling; mortality; pines; top-kill; Wildfire